Mechanism of enhanced oral absorption of hydrophilic drug incorporated in hydrophobic nanoparticles - Lv, Liang-Zhong (Dove Medical Press, 2013)
Hydroxysafflor yellow A (HSYA) is an effective ingredient of the Chinese herb Carthamus tinctorius L, which has high water solubility and low oral bioavailability. This research aims to develop a hydrophobic nanoparticle that can enhance the oral absorption of HSYA. Transmission electron microscopy and freeze-fracture replication transmission election microscopy showed that the HSYA nanoparticles have an irregular shape and a narrow size distribution. Zonula occludens 1 protein (ZO–1) labeling showed that the nanoparticles with different dilutions produced an opening in the tight junctions of Caco-2 cells without inducing cytotoxicity to the cells. Both enhanced uptake in Caco-2 cells monolayer and increased bioavailability in rats for HSYA nanoparticles indicated that the formulation could improve bioavailability of HSYA significantly after oral administration both in vitro and in vivo.